A two family house built to passive house standard in the north of Sweden – environmental system performance - Jonasson, Jonas; Danielski, Itai; Svensson, Michelle; Fröling, Morgan (Mittuniversitetet, Avdelningen för ekoteknik och hållbart byggande, 2014)
A life cycle assessment (LCA) of a low energy / passive house in northern Sweden, including building materials and energy use is reported. The case study building is semi detached house for two families situated in Östersund (lat. 63°N), Sweden. Each apartment having a floor space of 160 m2 divided on two floors. The building was constructed during 2010 with a design meeting the requirements for Swedish passive houses as defined by the Forum for energy efficiency buildings (FEBY) and the Swedish center for zero energy houses (SCNH).When it comes to more sustainable buildings, energy use in the build environment has been in focus for some time. The life cycle assessment in this study reveals that the building materials can contribute significantly to environmental burdens of a residential building in northern Sweden. Energy efficiency, efficient use of good building materials and issues of appropriate design need to be discussed in the same context to move toward a more sustainable built environment.For energy efficient buildings in a energy system with renewably based energy carriers, building materials might give rise to a significant or even dominating part of the life cycle impact of a building. This give rise to considerations regarding choices of building materials as well as design of buildings to minimize such impact; while not forgetting social aspects impacted by building design.